PENGARUH PENCAMPURAN SEMEN TERHADAP KUAT GESER TANAH LEMPUNG LAMPOH KEUDE - Muhammad Zardi; Mukhlis Mukhlis (Center for Research and Community Service (LPPM) University of Abulyatama, 2015)
The aim of the tests was to investigate the influence of cement on clay of Lampoh Keude Village Kuta Baroe district Aceh Besar district. Results to be seen is parameters of shear angle (ø) and cohesion (c) of the direct shear test. Normal stress to be given to direct shear test is 0.305 kg/ cm2, 0.634 kg cm2 and 1.293 kg /cm2 with optimum moisture content obtained 23.15% and the dry volume weight 1.438 gr /cm2. This study tested three samples for each percentage mixture of 0%, 4%, 8%, 12% and 16% with one day curing period. The amount of specimen without cement mixture was made of 3 specimens and without cement mixture was made of 12 specimens for 3 repetitions testing. Soil testing in the lab include testing the physical properties of the native land, the mechanical properties of the native land and land with a cement mixture. Based on the testing of the physical properties of the native land, AASHTO classifying soil in group A-7-6 (11) and USCS classifying soil as a silt and clay in CH group. The addition of cement shows the stability of direct shear tests with increases of cohesion (c) and friction angle (ø) is 0% cement is c = 0.797 kg/cm2 and ø = 31.45o, 4% cement is c = 1.326 kg/cm2, ø = 36,22o, 8% cement is c = 1.529 kg/cm2 and ø = 38,55o, 12% cement is c= 1.950 kg/cm2, ø = 38,11o and 16% cement is c = 2.084 kg/cm2, ø = 39,01o. Direct shear test results by mixing cement on clay showed an increase cohesion (c) and friction angle (ø) parameters.